Recommendations to the Society for Epidemiologic Research for Further Promoting Diversity and Inclusion at the Annual Meeting and Beyond. Issue 10 (30th June 2020) - Zhang, Mingyu; Jarrett, Brooke A; Althoff, Keri N; Burman, Frances S; Camarata, Laura; Coburn, Sally B; Dickerson, Aisha S; Foti, Kathryn; Kaur, Maneet; Leifheit, Kathryn M; Malone, Jowanna; Moore, Ebony A; et al.
Abstract: Increasing diverse engagement in the Society for Epidemiologic Research (SER) will positively impact the field of epidemiology. As the largest and longest-running epidemiologic society in North America, SER has long been a pioneer in promoting diversity and inclusion. A recent survey of SER members, however, showed there is still room for improving diversity, inclusion, representation, and participation in the Society. In this commentary, as members of both the SER and the Johns Hopkins Bloomberg School of Public Health Department of Epidemiology's Inclusion, Diversity, Equity, Anti-Racism, and Science (Epi IDEAS) Working Group, we recommend 4 goals for the SER Annual Meeting and beyond: 1) convene epidemiologic researchers with diverse backgrounds and ideas; 2) promote an inclusive environment at the SER Annual Meeting; 3) develop, compile, and disseminate best practices to honor diversity in epidemiologic research; and 4) increase prioritization of health disparities research and methods. We also suggest strategies for achieving these goals so that SER can better include, support, and elevate members from historically disadvantaged groups. While our recommendations are tailored specifically to SER, the greater epidemiologic and academic communities could benefit from adopting these goals and strategies within their professional societies and conferences.